If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2y + 3) = -2(3y + -4) Reorder the terms: 6(3 + 2y) = -2(3y + -4) (3 * 6 + 2y * 6) = -2(3y + -4) (18 + 12y) = -2(3y + -4) Reorder the terms: 18 + 12y = -2(-4 + 3y) 18 + 12y = (-4 * -2 + 3y * -2) 18 + 12y = (8 + -6y) Solving 18 + 12y = 8 + -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. 18 + 12y + 6y = 8 + -6y + 6y Combine like terms: 12y + 6y = 18y 18 + 18y = 8 + -6y + 6y Combine like terms: -6y + 6y = 0 18 + 18y = 8 + 0 18 + 18y = 8 Add '-18' to each side of the equation. 18 + -18 + 18y = 8 + -18 Combine like terms: 18 + -18 = 0 0 + 18y = 8 + -18 18y = 8 + -18 Combine like terms: 8 + -18 = -10 18y = -10 Divide each side by '18'. y = -0.5555555556 Simplifying y = -0.5555555556
| 3(x-4)x-7=4x+9 | | m/5-9=20 | | 11x/21-9=x/7+31 | | (a-1/9)-(3a+3/8)=(41-8/4) | | 169=x^2+x^2-14x+49 | | 1/2(8x-4)=3x+5 | | y/4.2=-10 | | (4w+9)(7-w)=0 | | -6x-6y=18 | | x/1.5= | | -4+c+13=-5 | | 8/2+7=5/2+1 | | 5/6x-1/5+4=7/10x | | b/19-2=-4 | | .25x=2.75 | | 15a-8=10a+7 | | 3x+21-4x=40 | | 6-x=x+3 | | 0.14x+0.8(x-1)=0.01(2x-3) | | 14.5+z=-4 | | 1/2x=-3 | | 25x-4=0 | | 4a-2=5a+5 | | 108-7x=11x+24 | | 2(2x-1)+4=26 | | 5t+4=-16 | | 4v-9=56 | | -9y+5=-3y-17 | | -12a=132 | | 0.17x+0.4(x-4)=0.01(2x-3) | | 11-7x=80-28x | | 0=2x^2-14x-120 |